Termites are the main dung removals in a degraded landscape in Brazil - Alves, Frederico R.; Aguilera-Olivares, Daniel; Rocha, Mauricio Martins; Arab, Alberto (Frontiers in Ecology and Evolution, 2022)
Termites are one of the most relevant groups for recycling nutrients and keeping the flow of energy in ecosystems. Although their role as lignocellulose decomposers is the focus of studies, they also act as dung recyclers, but their importance in this process is poorly understood. Here we performed manipulation experiments to determine dung removal by termites in forest remnants and cattle pastures in a fragmented Atlantic Forest landscape. We used wire bags of different mesh sizes placed along transects in three forest fragments and pastures for ten days to compare the contribution of termites and other coprophagous macroinvertebrates to dung removal. Our results indicated that termites removed more dung in pastures than in the forest fragments. In addition, dung beetle exclusion significantly reduced the percentage of dung removal within forest fragments, but not on pastures, indicating termites are important dung recyclers in pastures.